Meditating Masculine Anxiety and (Post) Colonial Space in Lubis's Harimau! Harimau! and Patterson's Man-Eaters of Tsavo - Hidayatullah, Danial (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2023)
This research is aimed at probing and comparing the masculine anxiety in colonial spaces of Lubis’s Harimau! Harimau! and Patterson’s The Man-eaters of Tsavo investigate similarities and diﬀerences between the subject position, the psychological impacts, and the psychic discourse of colonized and colonizer’s masculinities and male anxiety in terms of the colonial narrative. This comparison is essential for the subject position, and the psyche in the colonial narrative is claimed to be universal, which is not entirely true. Connell’s theory of masculinity is applied to investigate how the values of masculinity shape colonial experiences. This research employs a narratological method - employing the concept of focalization to scrutinize how the subject who see exercise the power of seeing and eventually constructing the subject position and the psyche of colonized and colonizer - psychoanalytic as well as postcolonial reading to reveal the psychological impact - of the character’s anxiety. The results are: 1) In both stories, the colonial settings are portrayed similarly even though the writers of the two stories came from diﬀerent continents (West and East). 2) In a hostile colonial setting, the colonizer and the colonized are constructed similarly in dealing with anxiety. However, when colonized are in the subject position, they are constructed as anal-erotic characters or anti-heroes. Simultaneously they are described as devout Moslems. Meanwhile, the European counterpart, although not described as a devout Christian, was the story’s hero. As an Indonesian novel, this marks the point that it falls into Western colonial narratives’ patterns.